The motivational values of social entrepreneurs - Lönnström, Anu (2015)
The main goal of this research is to understand what kind of motivational values social entrepreneurs have (motivational types of values), how social entrepreneurs prioritize these values (value prioritization) and if these values had an impact on becoming a social entrepreneur and continuing to work as one (impact of the values). The research on social entrepreneurship has largely ignored for-profit social entrepreneurship and the purpose of this research is to contribute to this shortcoming by taking the for-profit entrepreneurs’ perspective. A qualitative case study was chosen as a research method and the empirical data was gathered by interviewing for-profit social entrepreneurs using a theme interview.